Feelings about pregnancy and mother-infant bonding as predictors of persistent psychological distress in the perinatal period: The Japan Environment and Children's Study. (August 2021) - Tokuda, Narumi; Kobayashi, Yoshiko; Tanaka, Hiroyuki; Sawai, Hideaki; Shibahara, Hiroaki; Takeshima, Yasuhiro; Shima, Masayuki; ,; Kamijima, Michihiro; Yamazaki, Shin; Ohya, Yukihiro; Kishi, Reiko; et al.
Abstract: Feelings about pregnancy and mother-infant bonding are associated with maternal mental health before and after childbirth. The current study examined factors associated with persistent distress at 12 months after childbirth among mothers with psychological distress in the first trimester, using data from the Japan Environment and Children's Study (JECS). Feelings about pregnancy were assessed using a questionnaire in the first trimester, and maternal mental health was assessed using the Kessler 6 (K6) in the first trimester and at 12 months after childbirth. In addition, mother-infant bonding was assessed using the Mother-to-Infant Bonding Scale Japanese version (MIBS-J) at 12 months after childbirth, and 5 items from the MIBS-J at one and six months after childbirth. Among the 97, 415 mothers registered in the JECS, 24, 324 mothers with psychological distress (K6 ≥ 5) in the first trimester were included in this analysis. The relationships between persistence of psychological distress at 12 months after childbirth with feelings about pregnancy and mother-infant bonding were analyzed. Both maternal negative feelings about pregnancy in the first trimester and mother-infant bonding after childbirth were significantly associated with persistent psychological distress at 12 months after childbirth (β = 0.02, p = 0.001 and β = 0.35, p < 0.001, respectively). The indirect effect of feelings about pregnancy on persistent distress through mother-infant bonding was also observed (β = 0.06, p < 0.001). These findings indicate that mother-infant bonding after childbirth may be important for improving the mental health of mothers with prenatal psychological distress. Highlights: We assessed predictors of persistent psychological distress in the perinatal period. Prenatal distress persisted among mothers with negative feelings about pregnancy. Poor mother-infant bonding was associated with persistence of prenatal distress. Feelings about pregnancy affect persistent distress through mother-infant bonding. To improve maternal psychological distress, mother-infant bonding may be important.